Boston type 1 keratoprosthesis: Updated perspectives - Manachai Nonpassopon (2020)
© 2020 Nonpassopon et al. The use of Boston type 1 keratoprosthesis (BKPro) has significantly increased worldwide. It is no longer considered a procedure of last resort but a reasonable option for patients with otherwise poor prognosis for a traditional penetrating keratoplasty. BKPro was approved by the Food and Drug Administration in 1992 for bilateral severe corneal blindness due to multiple corneal transplant failure. Over the years, indications have extended beyond recurrent immunologic rejection to include other conditions such as chemical injury and other causes of bilateral limbal stem cell deficiency, extensive corneal neovascularization, neurotrophic corneas and hypotony, among others. Numerous advances in the design of the BKPro, improvement of preoperative, intraoperative and postoperative management have resulted in favorable outcomes and a reduction in postoperative complications. Accordingly, many studies have shown that implantation of this device is highly effective in restoring vision with very good short-term outcomes. However, due to the lifetime risk of sight-threatening complications after BKPro implan-tation, a longer follow-up period should provide outcomes that are more realistic. In this review, the authors examined only the results of publications with an average of at least 2 years of follow-up. The overall intermediate to long-term visual outcomes and retention rate in BKPro seem to be favorable. However, autoimmune diseases and cicatrizing conditions continue to show a higher incidence of postoperative complications that require further management.